When the cornfield dries up, love dries up too: Climate, gender and migration in Guatemala - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
This carousel tells the story of how climate change, gender inequality, and migration intersect in rural Guatemala, and why migration decisions are rarely just about climate alone. Drawing on research across four communities, it shows how repeated droughts, erratic rainfall, and rising temperatures have damaged maize and coffee harvests, deepening poverty and debt. For some families, migration becomes a survival strategy; for others, especially the poorest and women without support, leaving is not an option. The carousel highlights how climate stress intensifies existing gender inequalities, increasing food insecurity, health risks, and gender-based violence. Through community-led research and testimonies, including the phrase “when the cornfield dries up, love dries up too,” it emphasizes that people are not passive victims. Communities proposed practical, interconnected solutions, underscoring the need to fund locally designed, gender-responsive responses rather than one-size-fits-all interventions